An Analysis of the Consistency of Discrete Mathematics Content in the Teacher Education Curriculum with the Actual Needs of Lower Secondary Mathematics Instruction - KEOMOUNGKHOUN, Daomanolack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study employs a Mixed Methods Research design with three primary objectives were to: 1) investigate the Discrete Mathematics content taught at Savannakhet Teacher Training College; 2) assess the content needs and pedagogical skills required for lower secondary mathematics instruction; and 3) analyze the consistency of the Discrete Mathematics curriculum relative to actual instructional requirements. The sample consisted of 15 mathematics teachers from Savannakhet Teacher Training College and 60 mathematics teachers who graduated from teacher training colleges and are currently teaching in secondary schools within Savannakhet and Khammouane provinces. The research instruments included document analysis of the curriculum, a Likert scale questionnaire, and semi-structured interviews. Data were analyzed using mean, standard deviation, consistency index and content analysis. The findings revealed that: 1) The Discrete Mathematics content in the teacher education curriculum emphasizes comprehensive fundamental theories, yet its integration into practical classroom application remains limited; 2) The actual needs of teachers are at the highest level for both Subject Matter Knowledge (SMK), particularly in fundamental number systems ( = 4.81, SD = 0.45), and Pedagogical Content Knowledge (PCK), specifically regarding the ability to address student misconceptions ( = 4.77, SD = 0.50); 3) The overall consistency index was high (CI = 0.78); however, the integration of SMK into PCK demonstrated the lowest consistency (CI = 0.65). Consequently, the study recommends increasing activities that focus on developing Pedagogical Content Knowledge (PCK) skills to effectively bridge the gap between theoretical knowledge and professional practice.